A New Design of Double Stator Permanent Magnet Flux Switching Machine Employing H-Configuration Modular Rotor Using Finite Element Analysis - Mostaman, Nur Afiqah; Jenal, Mahyuzie (Evolution in Electrical and Electronic Engineering, 2022)
Permanent Magnet Flux Switching Machine (PMFSM) are widely used in medium to high scale industries of electrical vehicles. Due of the PMFSM flux's current focus on the utilizable stator, PMFSM has gained a lot of interest in motor design for the armature windings and permanent magnet excitation source and the salient rotor pole which is simple yet robust. However, a double stator of Alternate Circumferential Radial Flux (AlCiRaF) with a salient rotor of PMFSM has passed down the flux cancellation, high winding losses and high iron losses which can decrease the motor's efficiency and torque. Therefore, to overcome these weaknesses and disadvantages, in this study, a double stator PMFSM by employing H-configuration modular rotor was designed to improve the results of torque and efficiency of the motor. This newly designed motor is suitable to be used domestically for electric vehicles. The primary goals of this project are to develop and design for upgrading the torque density and the motor efficiency to be used in an electric vehicle that has a good system and flexible use in industries where the motor design developed can reduce the losses of the motor. In this project, the design of the double stator of PMFSM with modular rotor used JMAG Designer 16.0 is used as the main software to design this project from design to simulation step to observe the motor. The result shows this double stator of PMFSM with a modular rotor have high torque and efficiency compared to the design of double stator AlCiRaf of PMFSM with a salient rotor.